Adsorption, aggregation, and desorption of proteins on smectite particles - Kolman, Krzysztof (Langmuir : the ACS journal of surfaces and colloids, 2014)
We report on adsorption of lysozyme (LYS), ovalbumin (OVA), or ovotransferrin (OVT) on particles of a synthetic smectite (synthetic layered aluminosilicate). In our approach we used atomic force microscopy (AFM) and quartz crystal microbalance (QCM) to study the protein-smectite systems in water solutions at pH ranging from 4 to 9. The AFM provided insights into the adhesion forces of protein molecules to the smectite particles, while the QCM measurements yielded information about the amounts of the adsorbed proteins, changes in their structure, and conditions of desorption. The binding of the proteins to the smectite surface was driven mainly by electrostatic interactions, and hence properties of the adsorbed layers were controlled by pH. At high pH values a change in orientation of the adsorbed LYS molecules and a collapse or desorption of OVA layer were observed. Lowering pH to the value ≤ 4 caused LYS to desorb and swelling the adsorbed OVA. The stability of OVT-smectite complexes was found the lowest. OVT revealed a tendency to desorb from the smectite surface at all investigated pH. The minimum desorption rate was observed at pH close to the isoelectric point of the protein, which suggests that nonspecific interactions between OVT and smectite particles significantly contribute to the stability of these complexes